The Impact of Gamification on Problem Solving Skills in STEM Education: A Meta-analysis - Ellina Rienovita; Arifin Arifin; Venty Sopacua; Wahyu Kumala Sari; Bambang Mardi Sentosa; Mia Aina; Hersiyati Palayukan; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2024)
This meta-analysis aimed to investigate the impact of gamification on problem-solving skills in STEM education. The study analyzed 16 studies that compared gamification-based interventions with traditional teaching methods in primary and early secondary education. The results showed moderate positive effects of gamification on problem-solving skills, with a weighted mean effect size of 0.67. Additionally, the analysis revealed significant heterogeneity between studies, suggesting that the effectiveness of gamification varied across different contexts. Moderator analyses indicated that primary school students benefited more from gamification-based interventions than secondary school students, but gender did not have a significant moderating effect. The study highlights the potential benefits of gamification in enhancing problem-solving skills in STEM education, particularly for primary school students. However, the findings also suggest that the effectiveness of gamification may depend on various factors, such as the specific context and student demographics, which warrants further investigation.